Irbesartan in Marfan syndrome (AIMS): a double-blind, placebo-controlled randomised trial. Issue 10216 (21st December 2019) - Mullen, Michael; Jin, Xu Yu; Child, Anne; Stuart, A Graham; Dodd, Matthew; Aragon-Martin, José Antonio; Gaze, David; Kiotsekoglou, Anatoli; Yuan, Li; Hu, Jiangting; Foley, Claire; Van Dyck, Laura; et al.
Summary: Background: Irbesartan, a long acting selective angiotensin-1 receptor inhibitor, in Marfan syndrome might reduce aortic dilatation, which is associated with dissection and rupture. We aimed to determine the effects of irbesartan on the rate of aortic dilatation in children and adults with Marfan syndrome. Methods: We did a placebo-controlled, double-blind randomised trial at 22 centres in the UK. Individuals aged 6–40 years with clinically confirmed Marfan syndrome were eligible for inclusion. Study participants were all given 75 mg open label irbesartan once daily, then randomly assigned to 150 mg of irbesartan (increased to 300 mg as tolerated) or matching placebo. Aortic diameter was measured by echocardiography at baseline and then annually. All images were analysed by a core laboratory blinded to treatment allocation. The primary endpoint was the rate of aortic root dilatation. This trial is registered with ISRCTN, number ISRCTN90011794. Findings: Between March 14, 2012, and May 1, 2015, 192 participants were recruited and randomly assigned to irbesartan (n=104) or placebo (n=88), and all were followed for up to 5 years. Median age at recruitment was 18 years (IQR 12–28), 99 (52%) were female, mean blood pressure was 110/65 mm Hg (SDs 16 and 12), and 108 (56%) were taking β blockers. Mean baseline aortic root diameter was 34·4 mm in the irbesartan group (SD 5·8) and placebo group (5·5). The mean rate of aortic root dilatation was 0·53 mm per year (95% CI 0·39 to 0·67) in the irbesartan group compared with 0·74 mm per year (0·60 to 0·89) in the placebo group, with a difference in means of −0·22 mm per year (−0·41 to −0·02, p=0·030). The rate of change in aortic Z score was also reduced by irbesartan (difference in means −0·10 per year, 95% CI −0·19 to −0·01, p=0·035). Irbesartan was well tolerated with no observed differences in rates of serious adverse events. Interpretation: Irbesartan is associated with a reduction in the rate of aortic dilatation in children and young adults with Marfan syndrome and could reduce the incidence of aortic complications. Funding: British Heart Foundation, the UK Marfan Trust, the UK Marfan Association.